2013
DOI: 10.1016/j.crohns.2012.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors and risk of developing paediatric inflammatory bowel disease — A population based study 2007–2009

Abstract: We identified several risk and protective factors for developing IBD. Studies on the influence of environmental factors are important in our understanding of aetiology and phenotypes of paediatric IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
76
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(88 citation statements)
references
References 50 publications
8
76
1
3
Order By: Relevance
“…Both factors indicate that hormonal influences also may play a role at least for the risk of disease flares. • For breastfeeding, conflicting results have been reported [20,[67][68][69][70][71] . A meta-analysis could not conclusively decide whether there is a protective or even diseaseaggravating effect [72] .…”
Section: Environmental Factors Known To Play a Role For Disease Flaresmentioning
confidence: 83%
“…Both factors indicate that hormonal influences also may play a role at least for the risk of disease flares. • For breastfeeding, conflicting results have been reported [20,[67][68][69][70][71] . A meta-analysis could not conclusively decide whether there is a protective or even diseaseaggravating effect [72] .…”
Section: Environmental Factors Known To Play a Role For Disease Flaresmentioning
confidence: 83%
“…Moreover, some studies have demonstrated an inverse correlation between consumption of citrus fruits, fruit and vegetable juices vs. incidence of CD and UC [7,8]. According to the study carried out in Denmark in 118 patients with IBD and in several-hundred controls, high sugar intake significantly increased the risk of IBDs while consumption of large amounts of vegetables had protective effects [9]. To maintain the integrity of the intestinal mucosa, hence the intestinal barrier, it is essential to consume the products rich in fibre.…”
Section: Effects Of Diet On the Ibd Incidence And Coursementioning
confidence: 99%
“…Although the precise aetiology of CD, as well as the forces behind the changing epidemiology, remain unknown, most hypotheses propose that environmental factors are the predominant contributing force in the rise of CD rates and earlier disease onset [19,49,50] . The changing diet habits of Asian populations is one factor that may be responsible for the rising incidence [34,51] .…”
Section: Role Of Environmental Factors In CD Pathogenesis and Changinmentioning
confidence: 99%